Screening criteria of optimum carbon dioxide injection for enhanced coalbed methane recovery and prediction of carbon dioxide storage capacity: A case study in south sumatera basin, Indonesia - Pratama, E. (Italian Association of Chemical Engineering - AIDIC, 2017)
This study proposes the screening criteria for optimum CO2 injection to enhanced coalbed methane (ECBM) recovery as well as predicting CO2 storage capacity by developing a novel numerical model based on the characteristic of coal seams and CBM field in South Sumatera Basin, Indonesia. The comparison of primary and enhanced CBM recovery was analysed by performing production forecasting for 30 y of simulation. A sensitivity study was then conducted in order to examine the performance of ECBM under the influences of CBM reservoir properties which are fracture permeability, matrix porosity, reservoir temperature, and coal seam depth. In summary, the reservoir screening criteria for successful application of CO2-ECBM have been fully defined and proposed. The key criteria of reservoir characteristics for successful application of CO2- ECBM are likely to be homogeneous reservoir, simple structure, fracture permeability more than 2 mD, matrix porosity more than 0.5 , reservoir temperature less than 100 °C, and coal seam depth more than 500 m. Furthermore, the method for estimating CO2 storage capacity in coal seams has been proposed by simplifying the Original Gas in Place (OGIP) volumetric computation which is validated with the numerical model through sensitivity studies. The proposed equation is applicable for 100 gas saturation in coal matrix and adsorption process as the main and the only storage mechanism in coal seams. Copyright © 2017, AIDIC Servizi S.r.l..